MAHMOUD KASHGARI'S WORK “DEVONI DUKATIT TURK” IS AN IMPORTANT SOURCE FOR THE STUDY OF THE ETHNOGRAPHY OF THE TURKIC PEOPLES. (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
The article analyzes the scientific and practical significance of Mahmoud Kashgari's work “Divanu-lughat al-Turk” in the study of ethnography of the Turkic peoples. The work contains valuable information about the life, customs, language and culture of the Turkic peoples and is used as the main source in ethnographic research. The article highlights the content of the work, the methodological approach, and its role in the study of the cultural history and language of the Turkic peoples. The results of the study show the importance of Kashgar creativity for modern ethnographic and linguistic research.